Social Norms and Welfare State Dynamics - Assar Lindbeck; Sten Nyberg; Jörgen W. Weibull (The Research Institute of Industrial Economics (IUI), 2002)
The paper analyses the interaction between economic incentives and work norms in the context of social insurance. If the work norm is endogenous in the sense that it is weaker when the population share of beneficiaries is higher, then voters will choose less generous benefits than otherwise. We also discuss welfare-state dynamics when there is a time lag in the adjustment of the norm in response to changes in this population share, and show how a temporary shift in the unemployment rate may cause persistence in the number of beneficiaries.
Keywords: D19; D64; H31; Z13; 330; Welfare State; Social Norms; Social Insurance; Arbeitsethik; Sozialstaat; Sozialversicherung; Trittbrettfahrerverhalten; Neue politische Ökonomie; Theorie; Soziale Norm